A Clinical Audit of Postoperative Urinary Retention in the Postanesthesia Care Unit - McLeod, L.; Southerland, Kerry; Bond, J. (Elsevier, 2013)
Postoperative urinary retention (PUR) is a common postsurgical complication. Early detection and management of PUR is of particular concern to nurses working in the postanesthesia care unit (PACU) because a single episode of bladder distention may result in permanent bladder damage. A clinical audit (CA) was conducted that examined the risk factors that may contribute to the development of PUR in the PACU. The CA was conducted over a 1-week time period and used a data collection tool that was developed from the current literature. A total of 34 patients met the inclusion criteria for the CA, and a prevalence rate of 20.6% was reported, which was consistent with prevalence rates reported by larger research studies. Despite the small sample size of this CA, results suggested that PUR should be of concern to nurses in the PACU. Recommendations included the development and implementation of a guideline relating to bladder scanning in the PACU and modification of existing PACU discharge criteria to include bladder management.